UTILIZATION OF TIK-TOK APPLICATIONS IN PANDEMIC TIMES COVID-19 - Astalita Amir (Fox Justi : Jurnal Ilmu Hukum, 2020)
This paper has the title, "Utilization of the TikTok Application During the COVID-19 Pandemic". The purpose of this study is as a tool to find out the phenomenon of Tiktok application users in the midst of the Covid-19 pandemic, how the motives of Tiktok application users are, the actions of Tiktok application users and what is the meaning of using the Tiktok application in the midst of the Covid-19 pandemic. The research methods and methods that have been used by researchers in conducting this research are the Phenomenological method, with the type of qualitative research, and the data collection technique of research results is done by means of online interviews. The interviews conducted involved several users of the Tiktok application itself. Based on the results of the study, it was obtained that the motive for using the Tiktok application in the midst of the Covid-19 pandemic was as an entertainment medium. Furthermore